2017
DOI: 10.17219/pzp/70428
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive assessment of the return to mobility of patients after hip replacement surgery

Abstract: StreszczenieWprowadzenie. Endoprotezoplastyka ma na celu poprawę funkcji stawu i zmniejszenie bólu. Jest obecnie uznawana za skuteczną formę leczenia, która przynosi wiele korzyści. Przy próbie oceny powrotu pacjentów do sprawności ruchowej po alloplastyce stawu biodrowego zwrócono uwagę na stopień odczuwanego bólu przed zabiegiem i po nim, trudności w codziennych czynnościach i problemy w życiu zawodowym. Badania wykazały, że respondenci przed zabiegiem najczęściej odczuwali silny ból. Po operacji ankietowani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This was the result of postoperative rehabilitation, which was used by 95% of the study group. In their study, Stanek et al [18] showed that, as a result of implantation of a joint endoprosthesis, the degree of difficulty in performing all analyzed activities decreased significantly. This produced an increase in the independence of patients: the number of people requiring help from other people decreased from 37.5% to 20%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This was the result of postoperative rehabilitation, which was used by 95% of the study group. In their study, Stanek et al [18] showed that, as a result of implantation of a joint endoprosthesis, the degree of difficulty in performing all analyzed activities decreased significantly. This produced an increase in the independence of patients: the number of people requiring help from other people decreased from 37.5% to 20%.…”
Section: Discussionmentioning
confidence: 98%
“…This was accompanied by a significant increase in the group of patients in the "light" condition, from 68% to 92%, according to the Kotel et al [17], while the functional changes in the patients after hip arthroplasty were found to be very good and good. Stanek et al [18] reported that, as a result of hip arthroplasty, a significant decrease was observed in the number of patients with limited walking ability; limited hip joint mobility; pain in the hip, buttock, and thigh; and leg contracture. The ability of patients to climb and walk up and down stairs significantly improved.…”
Section: Discussionmentioning
confidence: 99%